Positive facilitators of diabetes management in emerging adults with type 1 diabetes—A qualitative analysis of blogs. Issue 3 (19th June 2020) - Johansen, Clea Bruun; Pouwer, Frans; Beck‐Nielsen, Henning; Rothmann, Mette Juel
Abstract: Introduction: Emerging adults (18‐30 years) with type 1 diabetes must manage a demanding chronic illness as well as navigate a life phase full of instability and transitions. Clinical care for this age group remains a challenge. An improved understanding of psychological facilitators of diabetes management may contribute to optimized clinical care to this age group. Aim: To explore which individual strategies facilitated emerging adults' diabetes management and what kind of support they regard helpful from peers, family and healthcare providers. Methods: Qualitative analysis of web blogs. We identified personal blogs by emerging adults with type 1 diabetes through a search at the websites for diabetes associations in Denmark, UK and the USA, a snowball search at identified blogs and an internet search (Google). Blog posts from approximately the last year were analysed with thematic analysis as described by Braun and Clarke. Results: We included 16 blogs from UK, the USA, Australia and Denmark, focusing on blog entries from 2017 to 2018. Several psychological facilitators of management of type 1 diabetes were identified. Positive individual strategies involved: developing a balanced approach to blood glucoses, sharing diabetes with peers and making space for emotional reactions. Supportive involvement from peers, family and health care providers included: normalization, emotional backup and a nonjudgmental attitude. Conclusion: Diabetes management in emerging adulthood can be facilitated by several individual strategies as well as by supportive involvement from peers, family and health care providers. It is worthwhile to further investigate how individual strategies as well as supportive involvement can be promoted in diabetes care. Abstract : A qualitative analysis of personal blogs written by emerging adults with type 1 diabetes documented psychological strategies that facilitated diabetes self‐management.